2019
DOI: 10.3390/nu11092249
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nutrition Education Intervention with and Without a Mobile Phone Application on Nutrition Knowledge Among Young Endurance Athletes

Abstract: Athletes often have significant gaps in their nutrition knowledge. Thus, the aim of this study was to investigate whether young Finnish endurance athletes’ nutrition knowledge and dietary intake can be improved through an education intervention with or without a mobile food application. Seventy-nine endurance athletes, 18.0 years (SD: 1.4), participated in this randomized, controlled intervention. We compared the effects of participatory nutrition education sessions alone (group EDU) to those including the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 37 publications
5
54
2
1
Order By: Relevance
“…The overall aim of nutrition education is to increase knowledge, support change and maintain appropriate dietary intake [ 19 , 41 ]. There is very little research on the optimal method to educate athletes, lectures and one-on-one counselling are the most common form of education intervention [ 19 , 42 ], but these can be impractical in many cases [ 41 , 43 ]. Nutritional support is usually offered on a part-time or consultancy basis, even in the professional environment, with limited time with the players [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall aim of nutrition education is to increase knowledge, support change and maintain appropriate dietary intake [ 19 , 41 ]. There is very little research on the optimal method to educate athletes, lectures and one-on-one counselling are the most common form of education intervention [ 19 , 42 ], but these can be impractical in many cases [ 41 , 43 ]. Nutritional support is usually offered on a part-time or consultancy basis, even in the professional environment, with limited time with the players [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore propose that the practitioners may need to be innovative in their approach to translate evidence-based nutritional advice into practice. Online platforms such as mobile applications (apps) could provide sports nutrition practitioners the opportunity to make nutrition education interventions more time-efficient and successful [ 41 , 44 ]. Digital health interventions have demonstrated to be successful in enhancing nutrition knowledge and improving individuals’ behaviours which resulted in increased vegetable intake in young adults [ 45 ], and successful weight loss in overweight individuals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, elite squash players should aim to increase their nutrition knowledge, as this may lead to greater dietary behaviours [ 21 ] and athletic ability [ 22 ]. Sport nutrition practitioners implement a variety of techniques to promote positive dietary behaviours, increasing nutrition knowledge in adolescent [ 47 , 55 , 71 – 76 ], collegiate [ 21 , 22 , 77 , 78 ] and elite athletes [ 79 ]. Future research should aim to quantify the effectiveness of a nutritional education intervention at increasing elite squash players nutrition knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This may especially be the case among high school athletes, many of whom have moved away from their parental home and started to take more responsibility over purchasing and preparing food. Indeed, some [ 18 , 19 ], but not all [ 20 ], studies have shown that older athletes have better nutrition knowledge compared to younger ones. Although there is mild evidence to suggest a positive association between nutrition knowledge and dietary intake, a very limited number of studies have used valid tools to assess both nutrition knowledge and dietary intake [ 21 ].…”
Section: Introductionmentioning
confidence: 99%